Narratives of illness in patient blogs: exploring personal voices and medical identity in Indonesian digital health discourse - Muhammad Syaifuddin (Indonesian Journal of Medical Linguistics, 2026)
Background: Digital health communication has expanded rapidly in Indonesia, where patient-authored blogs increasingly function as platforms for narrating illness experiences and negotiating medical identity. Objective: This study aims to examine how narrative structure, medical authority, and identity positioning are constructed and interactionally validated in Indonesian online illness narratives. Method: Using a qualitative corpus-informed design, this research analyzes 42 long-form patient blogs (≈247,000 words) and 812 associated comments through Narrative Analysis, Critical Discourse Analysis, and Positioning Theory. Results: The findings reveal a patterned narrative progression from diagnostic rupture to treatment trajectory and acceptance-oriented closure rather than restitution. Medical authority is not rejected but recontextualized through hybrid discourse combining biomedical terminology, embodied lexicon, and spiritual framing. Identity roles such as Believer, Educator, Fighter, and Family-Embedded Self are strategically mobilized and differentially reinforced through comment engagement. Implication: These findings indicate that digital illness narratives in Indonesia function as participatory spaces where medical authority and patient identities are actively negotiated and socially validated through narrative and interactional dynamics. Novelty: The novelty of this study lies in its integrative methodological triangulation and its demonstration that digital illness discourse in Indonesia constitutes a measurable site of authority negotiation and socially ratified identity construction within a non-Western sociocultural context.